Aproximación gráfica al avance de la frontera agraria moderna en Sudamérica. Estudio de caso en la provincia de Córdoba (Argentina) - Esteban Salizzi (Confins)
The work introduces a collection of schemes and thematic maps that represent the transformation process driven through the advance of the modern agrarian frontier over the northern departments of the province of Córdoba (Río Seco, Sobremonte and Tulumba), Argentina, among the 1990s and 2015. The visual materials prepared, along with their respective comments, synthesize the diversity of factors and dynamics that converge in the territorial expansion of the agribusiness productive model in the region, seeking to offer a comprehensive view of the phenomenon. This is an initiative interested in the use of graphic tools to face the challenges established by the study of the advance of modern agrarian frontiers, as well as other fronts of capital expansion.